2012
DOI: 10.1186/1471-5945-12-11
|View full text |Cite
|
Sign up to set email alerts
|

Eczema in early childhood is strongly associated with the development of asthma and rhinitis in a prospective cohort

Abstract: BackgroundThis study aimed to estimate the association between eczema in early childhood and the onset of asthma and rhinitis later in life in children.MethodsA total of 3,124 children aged 1–2 years were included in the Dampness in Building and Health (DBH) study in the year 2000, and followed up 5 years later by a parental questionnaire based on an International Study of Asthma and Allergies in Childhood protocol. The association between eczema in early childhood and the incidence of asthma and rhinitis late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
127
3
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(143 citation statements)
references
References 30 publications
10
127
3
3
Order By: Relevance
“…Regarding the severity of AD, Gustafsson et al 2 , Ricci et al 16 and Illi et al 17 found that children with high severity scores were at an increased risk of developing asthma. Kobyletzki et al 18 also found higher odds of developing asthma and AR for the moderate and severe forms of AD in comparison with the mild form of AD. Our results are slightly different from these, as we found a signifi cantly high risk of developing both diseases for the severe and moderate forms of AD, whereas 7 children with the mild form of AD also developed asthma.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Regarding the severity of AD, Gustafsson et al 2 , Ricci et al 16 and Illi et al 17 found that children with high severity scores were at an increased risk of developing asthma. Kobyletzki et al 18 also found higher odds of developing asthma and AR for the moderate and severe forms of AD in comparison with the mild form of AD. Our results are slightly different from these, as we found a signifi cantly high risk of developing both diseases for the severe and moderate forms of AD, whereas 7 children with the mild form of AD also developed asthma.…”
Section: Discussionmentioning
confidence: 93%
“…Th e results of various studies suggest that the early onset of AD is one of the most important risk factors for developing asthma and AR in children with AD. Kobyletzki et al 18 also point out that the early onset was a strong risk factor for the incidence of asthma (OR 3.44) and AR. Similar results were obtained by Illi et al 17 and Kelbore et al 19 , who suggest that early onset, but also parental atopic history, increase the odds of developing asthma and AR.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Sweden that followed 3124 children to 5 years reported that onset of eczema in the first year of life was associated with increased risk of developing asthma and rhinitis, while later onset of eczema was not [24]. De Benedetto [25] reviewed data suggesting that several epidermal alarmins may lead to a Th2 immune response when the skin barrier is compromised.…”
Section: Discussionmentioning
confidence: 99%
“…Eczema in early life is one of the strongest risk factors for subsequent development of atopic diseases such as allergic rhinoconjunctivitis or asthma in later life. 13 Cumulative incidence of eczema was considered to be the most relevant and reliable outcome measure because the chronic and relapsing course of the affliction may render point prevalence unreliable. 14 Eczema was diagnosed according to the criteria introduced by Hanifin, 15 based on the following features: pruritus, typical morphology and distribution, and a chronic relapsing course.…”
Section: Outcome Measuresmentioning
confidence: 99%